The misdiagnosis of interstitial cystitis/bladder pain syndrome in a VA population. Issue 7 (14th July 2019) - Skove, Stephanie L.; Howard, Lauren E.; Senechal, Justin; De Hoedt, Amanda; Bresee, Catherine; Cunningham, Timothy J.; Barbour, Kamil E.; Kim, Jayoung; Freedland, Stephen J.; Anger, Jennifer T.
Abstract : Aims: The complexity of Interstitial Cystitis/bladder Pain Syndrome (IC/BPS) has led to a great deal of uncertainty around the diagnosis and prevalence of the condition. Under the hypothesis that IC/BPS is frequently misdiagnosed, we sought to assess the accuracy of the ICD‐9/ICD‐10 code for IC/BPS using a national data set. Methods: Using the Veterans Affairs Informatics and Computing Infrastructure, we identified a random sample of 100 patients with an ICD‐9/ICD‐10 diagnosis of IC/BPS (595.1/N30.10) by querying all living patients in the Veterans Affairs (VA) system. We purposely sampled men and women equally to better understand gender‐specific practice patterns. Patients were considered a correct IC/BPS diagnosis if they had two visits complaining of bladder‐centric pain in the absence of positive urine culture at least 6 weeks apart. Patients were considered not to have IC/BPS if they had a history of pelvic radiation, systemic chemotherapy, metastatic cancer, or bladder cancer. Results: Of the 100 patients, 48 were female and 52 were male. Five had prior radiation, one had active cancer, and 10 had bladder cancer (all male), and an additional fifteen had insufficient records. Of the remaining 69 patients, 43% did not have IC/BPS. Of these patients who did not have IC/BPS, 43% complained only of overactive bladder (OAB) symptoms, which was more common in women (63%) than men (21%), P = .003. Conclusions: In our small sample from a nationwide VA system, results indicate that IC/BPS has a high misdiagnosis rate. These findings shed light on the gender‐specific diagnostic complexity of IC/BPS.